2018
DOI: 10.1159/000487266
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index as a Risk Factor for Toxicities in Patients with Advanced Soft-Tissue Sarcoma Treated with Trabectedin

Abstract: Objectives: Low body mass index (BMI) and/or low lean body mass have been shown to be risk factors for chemotherapy-related toxicities in a number of different cancers. However, no data are available regarding the role of BMI as a risk factor for developing toxicities related to the novel anticancer agent, trabectedin, in patients with soft-tissue sarcoma (STS). We evaluated the role of BMI as a risk factor for trabectedin-related toxicity in patients with STS. Methods: Data from 51 patients with metastatic/ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…Consequentially, the DCR is significantly lower in sarcopenic patients (P = 0.032). Studies on other solid tumors have found an association between sarcopenia and toxicity, and there is another body composition marker, namely the body mass index (BMI), that has been identified as a risk factor for toxicity in a/mSTS [28,29]. However, this correlation could not be found in our cohort (Data not shown).…”
Section: Discussioncontrasting
confidence: 64%
“…Consequentially, the DCR is significantly lower in sarcopenic patients (P = 0.032). Studies on other solid tumors have found an association between sarcopenia and toxicity, and there is another body composition marker, namely the body mass index (BMI), that has been identified as a risk factor for toxicity in a/mSTS [28,29]. However, this correlation could not be found in our cohort (Data not shown).…”
Section: Discussioncontrasting
confidence: 64%
“…Hematological toxicities induced by chemotherapy, such as leukopenia, were not defined as the primary outcome of this study, and probably the small sample size was not sufficient to eliminate type 1 error. In addition, individuals undergoing multiple types of treatment or who have compromised nutritional status, especially in the presence of changes in body composition, such as sarcopenia and cachexia, tend to have higher degrees of toxicity during chemotherapy, [4,[32][33][34][35] which was not observed in the studied population, who, for the most part, were overweight, without significant changes in CC, which is consistent with the literature about the nutritional status of women with breast cancer [32,33]. In addition, the participants in the present study were submitted to a unique therapeutic modality, without having undergone other types of cancer treatments, which may contribute to the long-term impairment of nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors for the incidence of FN in the low GNRI group were advanced age, poor PS, and poor nutritional status. In addition, low body weight and hypoalbuminemia are risk factors for FN in several chemotherapy regimens (19)(20)(21)(22)(23)(24). In this study, the low GNRI group also had significantly lower serum albumin levels and body weight at treatment initiation (Table I) and significantly more FN (Table II).…”
Section: Discussionmentioning
confidence: 55%